System-level Techniques for Analog Performance Enhancement - Song, Bang-Sup.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book shows readers to avoid common mistakes in circuit design, and presents classic circuit concepts and design approaches from the transistor to the system levels. The discussion is geared to be accessible and optimized for practical designers who want to learn to create circuits without simulations. Topic by topic, the author guides designers to learn the classic analog design skills by understanding the basic electronics principles correctly, and further prepares them to feel confident in designing high-performance, state-of-the art CMOS analog systems. This book combines and presents all in-depth necessary information to perform various design tasks so that readers can grasp essential material, without reading through the entire book. This top-down approach helps readers to build practical design expertise quickly, starting from their understanding of electronics fundamentals. .
Introduction -- Feedback -- Feedback Amplifiers -- Power Supplies and Regulators -- System Offset and Gain Corrections -- RF Sampled Data and Switching Techniques -- Opamp Gain and Nonlinearity Correction -- Image and Harmonic Rejection in Down Conversion -- System Performance Enhancement.
Keywords: Electronic circuits; Electronics; Electronic Circuits and Systems; Electronics and Microelectronics, Instrumentation